Sub-microsecond response time deep-ultraviolet photodetectors using α-Ga2O3 thin films grown via low-temperature atomic layer deposition - Lee, Seung Hyun; Lee, Kang Min; Kim, Young Bin; Moon, Yoon Jong; Kim, Soo Bin; Bae, Dukkyu; Kim, Tae Jung; Kim, Young Dong; Kim, Sun Kyung; Lee, Sang Woon (Journal of Alloys and Compounds, 2019)
A photodetector responding to deep-ultraviolet (DUV) wavelengths (λ = 200–300 nm) is developed via the growth of crystalline α-Ga2O3 thin films with a bandgap of 5.2 eV on sapphire (0006) substrates using atomic layer deposition (ALD), at a low temperature of approximately 250 °C. The achievement of crystalline α-Ga2O3 films at such a low temperature is viable owing to the lattice match between α-Ga2O3 and sapphire crystals, which is confirmed by X-ray diffraction measurements and high-resolution transmission electron microscopy analysis. Metal–semiconductor–metal photodetectors (active area of 30 × 30 μm2) using 10-nm-thick α-Ga2O3 films exhibit a rise time (time required for the photocurrent to increase from 10% to 90% of its final value under illumination) of 539 ns at λ = 266 nm. Such an ultrafast response to DUV with λ = 266 nm is maintained for 3-nm-thick α-Ga2O3 photodetectors, suggesting that our ALD process is adequate for obtaining high-quality ultrathin α-Ga2O3 films. Measurements of the wavelength-resolved photocurrents reveal that the α-Ga2O3 photodetectors respond selectively to DUV wavelengths (λ = 200–300 nm), without responding to other longer wavelengths (λ > 300 nm). The responsivity is maximized to 0.76 A/W at λ = 253 nm, and drops off at λ ≈ 300 nm (i.e., a cutoff wavelength). The dark current measured at 10 V is as low as 0.5 pA, and the signal-to-noise ratio reaches 104, both of which underpin the pristine material quality of the ALD-grown α-Ga2O3 films. We believe that the fabrication of photodetectors using α-Ga2O3 thin films at such a low temperature will provide an economically feasible solution for high-performance DUV detection and sensing applications.
Keywords: Cutoff wavelengths; Deep ultraviolet; Gallium oxides; Metal photodetectors; Pristine materials; Sensing applications; Wide band-gap material; X-ray diffraction measurements; Alpha gallium oxide; Atomic layer deposition; Deep-ultraviolet wavelengths; Photodetectors; Wide-bandgap materials